DIALECTICS OF RELIGION AND WOMEN: A REVIEW OF THE MANUSCRIPT OF HADĪYAT AL-NISĀ' FĪ TARGHĪB 'USHRAT AL-NISĀ BY MUHAMMAD AZHARI BIN KHATIB MA'ARUF AL PALEMBANI - Arfandi, Muhammad Fikri; Fauzan, Fauzan Fauzan; Nofrizal, Nofrizal Nofrizal (Marwah: Jurnal Perempuan, Agama dan Jender, 2025)
The Western feminist paradigm, which emphasizes individual freedom, often views religion as a source of suffering, oppression, and backwardness for women, thus religious teachings are considered an obstacle to achieving gender equality. This study aims to examine the discourse of women in the classical Islamic thought of the Indonesian archipelago through the manuscript Hadīyat Al-Nisā' Fī Targhīb 'Ushrat Al-Nisā by Muhammad Azhari bin Khatib Ma'aruf Al Palembani. This literature research uses a qualitative, descriptive-philosophical approach, with documentation and content analysis techniques, and deductive conclusion drawing. The results show that the manuscript contains rules on the rights, ethics, and roles of women in the family and society. These rules do not aim to discriminate as accused by Western feminism, but rather to protect the dignity and honor of women. This difference arises from the epistemological basis: Western feminism starts from a critique of patriarchy, while Islam is based on religion and morality. Thus, Islam places women in a noble position while protecting them from discrimination and subordination.